EXPLORING THE ROLE OF SOCIAL MEDIA IN ENHANCING EDUCATIONAL OUTCOMES - Shehzad Ahmed; Madiha Hussain; Yabaiz Saleem; Qaisar Ali Khan; Ira Mhae V. Catangay (International Journal of Contemporary Issues in Social Sciences, 2024)
This research seeks to find out how social media can be used to improve students’ motivation, creativity and performance. As prior research shows mixed results on the effects of social media on performance, this study will explore the relationship between social networking on academic performance and IM. The study uses an integrative approach that makes use of structural equation modelling (SEM) to confirm the proposed relationships between the usage of social media, the intrinsic motivation of the student, the student’s creativity and academic performance. Data was obtained from a sample of higher-learning students. The findings of this study show the usage of social media is positively correlated with academic performance and this relationship is also mediated by student’s intrinsic motivation. The level of motivation is made sure to go high for students who use social media in their academics hence creativity is higher and overall performance enhanced. These findings are consistent with motivation theories which have been proved in learning environments and the ability of social media to enhance achievements. It also offers another contribution to the body of knowledge in the area of the effects of social media on education to offer a roadmap on how the faculty and the ministries of education can harness the benefits of social media in realizing its intended objectives. Therefore, by developing factors that relate the use of social media to learning outcomes, this work offers a basis for future research to discover more about the use of the other aspects of technology in learning.